4 Prehospital recognition and antibiotics for 999 patients with sepsis: protocol for a feasibility study. (16th April 2018) - Moore, Chris; Bulger, Jenna; Morgan, Matt; Driscoll, Timothy; Porter, Alison; Islam, Saiful; Smyth, Mike; Perkins, Gavin; Sewell, Bernadette; Rainer, Timothy; Nanayakkara, Prabath; Okolie, Chukwudi; et al.
Abstract : Aim: Sepsis is common; it kills at least 44 000 people every year in the UK. Early recognition and management of sepsis has been shown to reduce morbidity and mortality of people with sepsis. Paramedics frequently come into contact with patients with sepsis, and are well placed to provide early treatment. This feasibility study aims to find out whether paramedics can collect blood cultures from and administer intravenous (IV) antibiotics to patients with sepsis. We will determine the feasibility, safety and acceptability of our trial design and data collection methods. Method: Paramedics will receive training to assist them to recognise sepsis using a screening tool, obtain blood cultures, and provide IV antibiotics. If sepsis is suspected, paramedics will randomly allocate patients to intervention or usual care using scratchcards. Patients will be followed up at 90 days using linked anonymised data to capture length of hospital admission and mortality. We will also collect self-reported health-related quality of life at this time. We will interview ten patients and hold a focus group with paramedics, to find out what they think about the intervention. Results: An intervention development group agreed upon the clinical protocol and training methods. Sixty paramedics have been trained. Patient recruitment will commence 1 st December 2017. Conclusion: At the end of this study we will make a recommendation about whether a fully-powered randomised controlled trial is warranted, and if so, we will develop a proposal for further research funding to answer questions regarding safety and effectiveness for patients, and benefit to the National Health Service. Conflict of interest: None Funding: PhRASe was funded by Health and Care Research Wales, Grant 1191. Chris Moore is the Chief Invesitgator.